African Indigenous Christianity of Pentecostal Type in South Africa in the Twentieth Century and Beyond: Another Reformation? - Müller, Retief (Theology Today, 2018)
Movements of reform and reformation have been highly significant in the history of Christianity for various reasons. Yet is it fair or appropriate to ascribe the term reformation to churches or groups not obviously belonging to the sixteenth-century series of events and movements usually associated with that term? This article engages with this question, especially in reference to the phenomenon of twentieth-century African Indigenous Christianity (AIC), which is often associated with terms such as African Initiated Christianity, and African Pentecostalism. I focus on South Africa as my context of reference. From this perspective I will more generally make the case that if the historical construct of reformation as a concept beyond sixteenth-century Northern and Western Europe could be useful at all, it will be in the ways in which one is able, or not, to draw parallels with some of the social consequences of those original movements. I am particularly interested in the relation between reformation and democracy. Therefore, my analysis of AIC history in South Africa is informed by the works of Witte, Woodberry, and McGrath.
paid
Keywords: African independent churches; Church renewal; Democracy and Christianity; Pentecostal churches; Pentecostal churches – Education; Pentecostal churches – Government; Reformation – Historiography; South Africa.; Zion Christian Church